Novel Series of Mononuclear Aluminum Complexes for High‐Performance Solution‐Processed Organic Light‐Emitting Devices. (26th January 2021) - Nakao, Kohei; Sasabe, Hisahiro; Shibuya, Yusuke; Matsunaga, Amane; Katagiri, Hiroshi; Kido, Junji
Abstract: Light metal complexes, such as lithium (Li), sodium (Na), magnesium (Mg), and aluminum (Al) complexes, are attractive candidates for the fabrication of thermally activated delayed fluorescent (TADF) materials. Nevertheless, mononuclear Al complexes with delayed fluorescence have not been developed so far. In this study, we successfully developed a novel series of highly luminescent Al complexes with two phenylacridine‐modified asymmetric acetylacetonate‐type ligands. These complexes exhibit high photoluminescence quantum yields (PLQYs) of up to 79 % in the solid state with a short delayed fluorescence lifetime of approximately 4 μs. Solution‐processed organic light‐emitting devices (OLEDs) using these Al complexes exhibit excellent performance with an external quantum efficiency of 17.5 % at 100 cd m −2 . This is the best performance in light metal‐based TADF OLEDs reported so far. The results are expected to guide the advancement of the next‐generation solid‐state lighting technology. Abstract : A high photoluminescence quantum yield of up to 79 % with a short delayed fluorescence lifetime of approximately 4 μs in the solid state is possible with a novel series of mononuclear aluminum complexes. Solution‐processed organic light‐emitting devices based on these Al complexes achieve a high external quantum efficiency of 17.5 % at 100 cd m −2 .